Estudo da Redução Foto(eletro)catalítica de CO2 em Produtos de Valor Agregado Utilizando Bi2MoO6 Modificado com La3+ - FRANCIELLE RODRIGUES GOMES STELO (2024)
The continuous use of fossil fuels raises serious concerns due to their significant CO2 emissions, which have global environmental, social, and economic impacts. In response, research and development of renewable technologies such as photovoltaic cells and photoelectrochemical cells are highlighted to reduce dependence on fossil fuels and mitigate negative impacts, reflecting efforts towards sustainable solutions aligned with environmental preservation. In this study, lanthanum (La)-modified bismuth molybdate (BMO) semiconductor was synthesized with different mass ratios of La and studied as a photocatalyst in the photocatalytic and photoelectrochemical CO2 reduction. Chemical composition analysis confirmed an experimental La ratio close to desired theoretical ratio in the photocatalysts. The addition of La altered the materials crystallinity, with a decrease in crystallite size associated with La3+ ionic segregation at grain interfaces, as evidenced by Rietveld refinement, specific surface area characterization, and grain interface area calculation. La segregation also influenced the morphology, resulting in diameter and thickness reduction of BMO nanoplates as La content increased. XPS technique confirmed changes in the local electronic structure of Bi surface and Mo atoms in the BMO lattice. This was evidenced by a shift to higher binding energies in the Mo 3d and Bi 4f peaks in La-doped samples. Tauc plots revealed similar bandgap values, with a trend of reduction as lanthanum content increased. For the liquid-phase photocatalytic reduction of CO2, the results highlighted the 0.5La-BMO photocatalyst as the most effective in producing ethanol (~3.5 µmol/gcat) and methanol (~25 µmol/gcat). In the gas phase, the unmodified BMO sample showed superior performance compared to the others, achieving the formation of more than 7 µmol/gcat of CO and 4 µmol/gcat of CH4 after 5 hours of irradiation. Additionally, La-BMO photoelectrodes were synthesized via the drop casting technique. The inclusion of La induced changes in the electronic and photoelectrochemical properties of the materials, resulting in a significant reduction in charge transfer resistance at the semiconductor/electrolyte interface, with the lowest value observed in the sample with a 1:1 mass ratio of La. Furthermore, the electronic band structure was investigated, and all synthesized samples revealed potential for direct production of methanol and ethanol from CO2. Due to the better photoelectrochemical efficiency, with a 90% increase in current density compared to the pure sample, the 1La-BMO composition was identified as the most promising photocathode. This sample was selected for photo-stability study and showed fluctuations in current over 5 hours of measurement under illumination at a potential of -0.6 V vs Ag/AgCl, indicating the need for electrode improvements for prolonged applications. These results highlight the significant potential of La-modified BMO material for photochemical and photoelectrocatalytic CO2 reduction applications. Additionally, La-BMO photoelectrodes were synthesized using drop casting technique. The inclusion of La induced changes in the electronic and photoelectrochemical properties of the materials, resulting in a significant reduction in charge transfer resistance at the semiconductor/electrolyte interface, with the lowest value observed in the 1:1 La:Bi mass ratio sample. Furthermore, through XPS-collected valence band spectrum, electronic band structure could be investigated, and all synthesized samples showed potential for direct CO2 conversion into methanol and ethanol. Due to the better response in photoelectrochemical efficiency, with a 90% increase in current density compared to the pure sample, the 1La-BMO composition was identified as the most promising photocathode, which also achieved the best results in obtained photon-to current conversion efficiency calculations. The sample was selected for the study of film photostability and showed fluctuations in current over 5 hours of measurement under illumination at a potential of -0.6 V vs Ag/AgCl, indicating the need for improvements in the electrode for prolonged applications. These results highlight the significant potential of La-modified BMO material for photochemical and photoelectrocatalytic applications for CO2 reduction.